Pengembangan Aplikasi E-Learning Berbasis Web Menggunakan Model Waterfall di Sekolah Dasar Masehi Tanggaba - Meriana Malo; Vinsensius Aprila Kore Dima; Agustina Purnami Setiawi (Router : Jurnal Teknik Informatika dan Terapan, 2025)
This research aims to develop a web-based e-learning application at Sekolah Dasar Masehi Tanggaba by applying the Waterfall software development model. The background of this study stems from the need for interactive, flexible, and easily accessible learning media in the digital era, considering that conventional face-to-face methods are still predominantly used in schools. The Waterfall model was chosen because it provides a systematic workflow through the stages of requirements analysis, system design, implementation, testing, and maintenance. Data collection was carried out through observations, teacher interviews, and documentation studies to identify the actual needs of users.The results of this study produced an e-learning application with key features, including learning material management, interactive quizzes, discussion forums, and automated assessment. Teachers can upload structured materials and assignments, while students can access learning content, complete exercises, and interact through forums more flexibly. System testing was conducted using the black box method to ensure that each function runs according to user requirements and specifications. Based on the testing results, the application was proven to function properly, be practical to use, and effective in supporting the learning process. Teachers found it helpful in managing materials and assignments, while students experienced more independent and interactive learning that was not limited to the classroom. Therefore, the developed e-learning application can be considered valid, practical, and effective as a supporting learning medium in elementary schools and has the potential to improve learning quality in the digital era.